Multi-criteria supplier selection using fuzzy analytic hierarchy process: case study from a Brazilian railway operator - Santis, Rodrigo Barbosa de; Golliat, Leonardo; Aguiar, Eduardo Pestana de (Brazilian Journal of Operations & Production Management, 2017)
The supplier selection problem has been discussed in literature within the supply chain management subject and it is extremely important due to its impact on the entire supply chain configuration, strategy and performance. This work presents a decision model based on the fuzzy analytic hierarchy process method and its application in a real case of maintenance supplier selection in a large Brazilian railway operator. Eight criteria were adopted - technical capacity, financial status, relationship, operations management, security management, infrastructure, historic performance and costs - for evaluating five potential suppliers. In the case study, both first and second ranked suppliers by the method have been selected by the company for providing the services and the model was adopted as a standard procedure within the organization for contracts over US 300,000.